90-Days Repeated Dose Oral Toxicity Study of Sharbat-e-Deenar (A Hepatoprotective Unani Herbal Formulation) - Gulam Mohammed Husain; Tasleem Ahmad; Syeda Hajra Fatima; Ghazala Javed; Munawwar Husain Kazmi; Mohd Urooj (Tehran University of Medical Sciences, 2021)
Sharbat-e-Deenar (SDR) is a compound Unani pharmacopoeial formulation recommended for the treatment of Waram-e-Kabid (hepatitis), Waram-e-Rahem (uterine inflammation/ Pelvic Inflammatory Diseases), Yarqan-e-Suddi (obstructive jaundice), and Istisqa (ascites). The current study was carried out to investigate repeated dose oral toxicity study of SDR for 90 days in Sprague dawley (SD) rats. SDR was orally administered (gavage) at the doses of 4, 10 and 20 mL/kg bw/day. A periodic observation was performed for mortality, morbidity and any clinical sign of toxicity. Changes in body weight and feed consumption were observed weekly throughout study duration. After the treatment duration of three months, animals were anaesthetized and blood samples were subjected to haematological investigation and serum was subjected to different biochemical estimation. Gross necropsy was performed and internal organs/ tissues were processed for histopathological investigation. Treatment with SDR showed no incidence of mortality and no clinical sign of systemic toxicity. Body weight showed pattern of weight gain except significance decrease at mid and high dose at 13th week of study duration. Feed consumption exhibited a significant decrease as compare to control. Haematology and biochemistry profile found normal except certain isolated changes which was considered toxicologically not significant as the values lies in the normal physiological range. There were no changes observed in the gross necropsy and relative organ weight data of control and SDR treated rats. It is reported that few of the animals showed changes in liver at mid (2.5 times of therapeutic equivalent dose) and high dose (5 times of therapeutic equivalent dose) in SDR treated animals that may be attributed to SDR treatment, however, associated liver function parameters like ALT, AST and ALP did not show any alteration of liver function. Based on the results of this study, it may be indicated that liver may be the target organ for toxicity if SDR is used above recommended therapeutic dose for longer duration.